Assessment of logistics efficiency and value of supply chains on the way of the New Silk Road countries in the context of the "Belt - Road" megaproject - Samiyeva, G.; Koichubayev А.; Tolysbaev , B. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2022)
The relevance of this article is determined by the significance of the strategic initiative "Belt - Road (BR)" both for the world economy as a whole and for the development of the countries directly included in this project. This article explores the impact of the BR Initiative on strengthening investment relations between Central Asia and China. The authors revealed that the implementation of the initiative is provided by the financial structures (European Bank for Reconstruction and Development, Asian Development Bank, Silk Road Fund, foreign direct investment of China), as well as bilateral agreements in the economic, investment and cooperation. The BR initiative was established by the PRC and supported in the Republic of Kazakhstan by Elbasy N.A. Nazarbayev in 2013. Nowadays BR initiative continuing in Kazakhstan as a political course by the President of the Republic of Kazakhstan K. Tokayev. It has been proved for implementation as essential project for development of transport and logistics infrastructure, has a positive impact for diversification of logistics routes for the supply of Chinese goods to the European market, and aimed at increasing the volume of trade and economic cooperation of all countries of Central Asia and China.